Historical patterns of fire severity and forest structure and composition in a landscape structured by frequent large fires: Pumice Plateau ecoregion, Oregon, USA - Hagmann, R. Keala; Merschel, Andrew G.; Reilly, Matthew J. (Landscape ecology, 2019)
Context Lack of quantitative observations of extent, frequency, and severity of large historical fires constrains awareness of departure of contemporary conditions from those that demonstrated resistance and resilience to frequent fire and recurring drought. Objectives Compare historical and contemporary fire and forest conditions for a dry forest landscape with few barriers to fire spread. Methods Quantify differences in (1) historical (1700–1918) and contemporary (1985–2015) fire extent, fire rotation, and stand-replacing fire and (2) historical (1914–1924) and contemporary (2012) forest structure and composition. Data include 85,750-ha tree-ring reconstruction of fire frequency and extent; > 375,000-ha timber inventory following > 78,900-ha fires in 1918; and remotely-sensed maps of contemporary fire effects and forest conditions. Results Historically, fires > 20,000 ha occurred every 9.5 years; fire rotation was 14.9 years; seven fires > 40,469 ha occurred during extreme drought (PDSI < − 4.0); and stand-replacing fire occurred primarily in lodgepole ( Pinus contorta var. murrayana ). In contemporary fires, only 5% of the ecoregion burned in 30 years, and stand-replacing fire occurred primarily in ponderosa ( Pinus ponderosa ) and mixed-conifer. Historically, density of conifers > 15 cm dbh exceeded 120 trees/ha on < 5% of the area compared to 95% currently. Conclusions Frequent, large, low-severity fires historically maintained open-canopy ponderosa and mixed-conifer forests in which large fire- and drought-tolerant trees were prevalent. Stand-replacing patches in ponderosa and mixed-conifer were rare, even in fires > 40,469 ha (minimum size of contemporary “megafires”) during extreme drought. In this frequent-fire landscape, mixed-severity fire historically influenced lodgepole and adjacent forests. Lack of large, frequent, low-severity fires degrades contemporary forest ecosystems.